Lingwistyczna reprezentacja artystycznego konceptu „ONA-KOBIETA” (na materiale autobiograficznej powieści Marii Arbatowej „Mam 46 lat”) - Oshchepkova, Anastasia (Studia Rossica Posnaniensia, 2016)
This work is related to the field of linguo-cultural studies, and also touches on the area of cognitive linguistics. The purpose is to describe the concept of “SHE — WOMEN” by analyzing text vocabulary which relates to a reduced style and which is distributed into lexical-thematic groups. The practical part of this article includes a description of each of the selected lexicalthematic groups. In the final part of the work, I describe the concept of “SHE — WOMEN” and draw conclusions.